On moving targets and magic bullets: Can the UK lead the way with responsible data linkage for health research?. Issue 11 (November 2015) - Laurie, G.; Ainsworth, J.; Cunningham, J.; Dobbs, C.; Jones, K.H.; Kalra, D.; Lea, N.C.; Sethi, N.
Highlights We explore key elements of good governance in health linkage. Adaptive reflexive governance models are essential. Two examples illustrate how we can achieve standardisation of practice. Distinct elements of governance compiled in a composite fashion tend to challenges.